Axon regeneration induced by environmental enrichment- epigenetic mechanisms - Tang, Bor Luen (Neural Regen Res, 2019)
Environmental enrichment is known to be beneficial for cognitive improvement. In many animal models of neurological disorders and brain injury, EE has also demonstrated neuroprotective benefits in neurodegenerative diseases and in improving recovery after stroke or traumatic brain injury. The exact underlying mechanism for these phenomena has been unclear. Recent findings have now indicated that neuronal activity elicited by environmental enrichment induces Ca(2+) influx in dorsal root ganglion neurons results in lasting enhancement of CREB-binding protein-mediated histone acetylation. This, in turn, increases the expression of pro-regeneration genes and promotes axonal regeneration. This mechanism associated with neuronal activity elicited by environmental enrichment-mediated pathway is one of several epigenetic mechanisms which modulate axon regeneration upon injury that has recently come to light. The other prominent mechanisms, albeit not yet directly associated with environmental enrichment, include DNA methylation/demethylation and N(6)-methyladenosine modification of transcripts. In this brief review, I highlight recent work that has shed light on the epigenetic basis of environmental enrichment-based axon regeneration, and discuss the mechanism and pathways involved. I further speculate on the implications of the findings, in conjunction with the other epigenetic mechanisms, that could be harness to promote axon regeneration upon injury.